2015
DOI: 10.21161/mjm.57213
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, identification and comparative evaluation of bioethanol tolerance and production capacity of isolated yeast strains from fermented date palm sap (Toddy)

Abstract: Aims: Toddy, an alcoholic beverage produced from naturally fermented date palm sap and commonly used as traditional drink in Southern India including Odisha, is a source of natural yeasts, capable of fermenting sugar to alcohol. The present study was carried out to isolate and identify predominant yeast strains from toddy, fermented date palm sap and to evaluate their ethanol tolerance and comparative bioethanol production capacity to select potential yeast strains for efficient bioethanol production for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In a study carried out by Dash et al . 6 , it has been reported that the isolated yeast strains can ferment all types of sugars expect lactose. This supports to the studies by Walker et al 21 who reported that all the yeast isolates ferment at least one type of sugar.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study carried out by Dash et al . 6 , it has been reported that the isolated yeast strains can ferment all types of sugars expect lactose. This supports to the studies by Walker et al 21 who reported that all the yeast isolates ferment at least one type of sugar.…”
Section: Resultsmentioning
confidence: 99%
“…However, a majority of these isolates which ferment glucose, galactose, maltose, sucrose and raffinose, belonged to the genus S. cerevisiae. The isolated strains were inoculated in TGY broth medium and incubated at different pH (3)(4)(5)(6)(7)(8) and temperature (20-40°C) conditions. All the strains isolated from soils samples were well grown at temperature 35°C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations